Students as Information Consumers: A Focus on Online Decision Making Process - Şendurur, E. (Springer New York LLC barbara.b.bertram@gsk.com, 2018)
There are many decision-making theories that explain how people decide to buy, click, read, or skip something online. Studies integrating the eye tracking methodology with decision-making processes state many assumptions. Based on a group of assumptions, the current study aims to compare the two search contexts and find if the assumptions are valid for both situations. The simultaneous mixed research methodology led to benefitting from both qualitative and quantitative data. Participants consist of 15 grad/undergrad volunteers from different departments. They were given two scenarios: a hotel search; an academic topic search. They were assigned to decide on the best three options. As they engaged in searching, their eye movements accompanied with think-aloud were recorded. The results indicated a consistency between espoused and enacted academic criteria in addition to the order of importance dimension, but neither of them was observed in everyday context. On the contrary to academic context, eye movements and espoused criterion/criteria were parallel in everyday context. Price and rating were popular criteria for the final decisions, and participants had their own heuristics related to them. Source and content for the academic context were popular, and the participants utilized heuristics, too. The fixations and visits on the popular areas were the maximum ones among others. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Academic Search; Eye Behavior; Online Decisions; Online Search